2013
DOI: 10.1136/annrheumdis-2012-eular.1748
|View full text |Cite
|
Sign up to set email alerts
|

OP0065 Tolerance and efficacy of rituximab in primary sjogren syndrome (TEARS): Results of a randomized controlled trial

Abstract: Background Current pharmacological treatments can improve the sicca symptoms but they are unable to modify the course of of primary Sjogren’s syndrome (pSS). There is evidence for a critical role of B cells in the pathogenesis of pSS. Both open labelled and small controlled studies suggested the efficacy of Rituximab (RTX) in specific subgroups of pSS. Objectives We conducted a multicenter, randomized, double-blind, placebo-controlled trial to evaluate the efficacy of RTX in a large group of patients with act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Previous studies have investigated the potential clinical efficacy and safety of rituximab therapy for primary Sjögren’s syndrome (69), but they too are limited by their small sample size, open-label design in some cases, and the lack of standardized treatment outcomes. These results are consistent with those reported in an abstract describing the results of a 122-patient, randomized, placebo-controlled study of rituximab therapy in primary Sjögren’s syndrome (34). In this study, rituximab therapy was not significantly more effective than placebo in improving by 30 mm or more at least two of the four 100 mm VAS scales evaluating dryness, pain, fatigue, and global disease activity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies have investigated the potential clinical efficacy and safety of rituximab therapy for primary Sjögren’s syndrome (69), but they too are limited by their small sample size, open-label design in some cases, and the lack of standardized treatment outcomes. These results are consistent with those reported in an abstract describing the results of a 122-patient, randomized, placebo-controlled study of rituximab therapy in primary Sjögren’s syndrome (34). In this study, rituximab therapy was not significantly more effective than placebo in improving by 30 mm or more at least two of the four 100 mm VAS scales evaluating dryness, pain, fatigue, and global disease activity.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study are consistent with those of a 122‐patient, randomized, placebo‐controlled study of rituximab therapy in primary Sjögren's syndrome, which was reported in the form of an abstract (33). In that study, rituximab therapy was not significantly more effective than placebo in improving by ≥30 mm the scores on at least 2 of the 4 100‐mm VAS scales evaluating dryness, pain, fatigue, and global disease activity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The objective is to select the patients who are most likely to benefit from the treatment in order to increase the chances of demonstrating treatment efficacy. For biologics or immunosuppressants, they might be a combination of factors, such as the inclusion of patients with active systemic complications, very early and/or biologically active disease 16 30. An alternative, or complementary, approach is to require a minimal ESSDAI score, such as moderate activity threshold (ESSDAI≥5), to ensure inclusion of patients with active disease.…”
Section: Discussionmentioning
confidence: 99%
“…This observation has some major implication for the conduct of clinical trials, particularly when assessing the effect of immunosuppressive therapy. First, this might explain why previous trials failed to demonstrate any effect of immunosuppressive or biologic treatments 18 19. Also, when evaluating such treatments, it might be preferable to assess its effect on the systemic manifestations for which it has been prescribed.…”
Section: Discussionmentioning
confidence: 99%